Effectiveness of Guided Inquiry Model in Enhancing Students' Critical Thinking on Light Waves - Sucy Lindriani; Iwan Permana Suwarna (Berkala Ilmiah Pendidikan Fisika, 2023)
This study examines how guided inquiry learning can be applied to the material of light waves in physics subjects. This study investigates the potential for increasing students' critical thinking skills. The research method used was a quasi-experimental design, creating the same conditions for the experimental and control groups in other aspects except for particular interventions in the experimental class. This research involved 60 samples of class XI high school students. The sample was divided into two groups (experimental and control) of 30 students each. The research data were obtained through pre-test and post-test from critical thinking instruments containing ten essay-type questions (validated, with validity 0.78 and reliability 0.96). Data were analyzed by parametric t-test on n-gain scores for each group. The results showed that the experimental group scored 0.526 and the control group 0.148. These results indicate differences due to intervention, where applying the guided inquiry model can significantly encourage the development of student's critical thinking skills. The research implications encourage teachers to apply this learning approach model in improving critical thinking skills so that students can be actively involved in facing complex challenges in everyday life. This study also emphasizes the need for curriculum development to improve critical thinking skills in various subjects.